Reinvenção do cânone: releitura paródica e transcontextaulização em Uma Viagem à India, de Gonçalo M. Tavares - Cruz, Kairo Lazarini da (Universidade Federal de São Carlos, 2020)
This Course Conclusion Work aims to analyze the novel Uma Viagem à Índia, by the Portuguese writer Gonçalo M. Tavares, from a proposal to verify the incidence of parodic resources in its composition. It is intended, here, to think how such reinvention opens a support for other reinterpretations, especially those of a cultural order, and how they all contribute to thinking the text under study within the scenario of a “new canon of Portuguese fiction” (REAL , 2012, p. 9). This work is based mainly on two guiding texts (HUTCHEON, 1985; REAL, 2012), in order to respectively examine the parodic processes contained in the work and ponder on some nuances of the literary context of Portuguese fiction from the 2000s onwards. In a second moment, through the reading of the Gonçalian text within the literary panorama of contemporary Portuguese fiction, the process of transcontextualization of Luís de Camões's Os Lusíadas, by the effect of parody, is specifically analyzed, and how, from this point onwards. resource, Gonçalo M. Tavares effectively contributes to thinking not only of another image of Portugal, but also of Europe itself, prefigured in the character Bloom.
Reinvention of the canon: parodic rereading and transcontextualization on Uma viagem à Índia, by Gonçalo M. Tavares
Keywords: Paródia; Transcontextualização; Ficção portuguesa contemporânea; Gonçalo M. Tavares; Parody; Transcontextualization; Portuguese contemporary fiction; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS